Natural materials modified mud mortar for rubble stone masonry: An experimental and numerical study - Li Xie; Xiao Hu; Zhenlin Chen; Wenjing Cai; Wenjie Zhang; Ying Hu; Zizhen Zeng (Case Studies in Construction Materials)
Rubble stone masonry is a long-standing construction. However, its binding material and mud mortar exhibit shortcomings, including low tensile and shear strength and poor water resistance. To overcome these limitations, researchers have initiated investigations into modifying mud mortar, specifically focusing on the influence of natural materials on their performance. This study used straw (0–1 wt%) and starch (0–7 wt%) as modifiers for mud mortar. The modified mortar underwent compression, straight shear, split tensile, water immersion, and abrasion tests to investigate its mechanical properties and water resistance. Additionally, electron microscope scanning was employed to reveal the modification mechanism of mud mortar at the microstructural level. The study results showed that 0.5 wt% straw/ 5 wt% starch was the optimal blended mortar. In contrast, for compressive strength, tensile strength, cohesion, and water absorption capacity, starch was better than straw, and for internal friction angle and abrasion resistance, straw was better than starch. The modification mechanisms of both were bridging and gelling effects, respectively. Lastly, finite element numerical simulations were employed in this study to analyze how modified mud mortar influences the shear performance of rubble stone masonry walls. The results demonstrated that adding both straw and starch substantially enhanced the shear strength and ductility of the walls. Specifically, the additions of 0.5 wt% straw and 5 wt% starch increased the shear strength by 18.12 % and 9.1 % and the ductility by 8.48 % and 0.83 %, respectively. This study significantly advances low-carbon, green buildings, and sustainable development.